Protocomputing Architecture over a Digital Medium Aiming at Real-Time Video Processing. (15th February 2018) - Tanibata, Aoi; Schmid, Alexandre; Takamaeda-Yamazaki, Shinya; Ikebe, Masayuki; Motomura, Masato; Asai, Tetsuya
Abstract : A protocomputational architecture is presented that implements the ancient reaction-diffusion model as a microelectronic hardware. A digital medium is selected for the physical mapping of the protoarchitecture as a way to benefit from reliable advanced integrated circuits fabrication technologies. The extraction of dense motion vector fields from textureless objects in a video sequence is selected as a realistic application. Real-time video processing results at 30 fps are achieved using an FPGA physical implementation of the proposed protoarchitecture.